Endoscopic time-lapse imaging of immune cells in infarcted mouse hearts - Jung, Keehoon; Kim, Pilhan; Leuschner, Florian; Gorbatov, Rostic; Kim, Jun Ki; Ueno, Takuya; Nahrendorf, Matthias; Yun, Seok Hyun (Circulation research, 2013)
Rationale:High-resolution imaging of the heart in vivo is challenging owing to the difficulty in accessing the heart and the tissue motion caused by the heartbeat.Objective:Here, we describe a suction-assisted endoscope for visualizing fluorescently labeled cells and vessels in the beating heart tissue through a small incision made in the intercostal space.Methods and Results:A suction tube with a diameter of 2 to 3 mm stabilizes the local tissue motion safely and effectively at a suction pressure of 50 mm Hg. Using a minimally invasive endoscope integrated into a confocal microscope, we performed fluorescence cellular imaging in both normal and diseased hearts in live mice for an hour per session repeatedly over a few weeks. Real-time imaging revealed the surprisingly rapid infiltration of CX3CR1+ monocytes into the injured site within several minutes after acute myocardial infarction.Conclusions:The time-lapse analysis of flowing and rolling (patrolling) monocytes in the heart and the peripheral circulation provides evidence that the massively recruited monocytes come first from the vascular reservoir and later from the spleen. The imaging method requires minimal surgical preparation and can be implemented into standard intravital microscopes. Our results demonstrate the applicability of our imaging method for a wide range of cardiovascular research.
Gesehen am 09.04.2021